In search of conclusive evidence on the trade-off and pecking order theories of capital structure: Evidence from the Johannesburg Stock Exchange. Issue 1 (2nd January 2018) - Chipeta, Chimwemwe; McClelland, David
ABSTRACT: This paper tests the validity of the trade-off and pecking order theories of capital structure for non-financial firms listed on the Johannesburg Stock Exchange. Firstly, we find that the pecking order model is superior than the partial adjustment regressions at rejecting random financing behaviour. Secondly, tests on real data show that partial adjustment regressions confirm (reject) target adjustment behaviour for off (on) target firms. However, when falsely generated random financing gaps are used, the GMM model records a higher error rate compared to the Censored Tobit Regressions. Lastly, we propose alternative tests of both theories, and show that the pecking order theory works well, except under conditions where firms with reported financial deficits are at the bottom of the pecking order.